Review of Coca Yes; Cocaine No: How Bolivia’s Coca Growers Reinvented Democracy - Kennemore, Amy; Postero, Nancy (European Review of Latin American and Caribbean Studies, 2019)
Coca Yes; Cocaine No: How Bolivia’s Coca Growers Reinvented Democracy, by Thomas Grisaffi, Duke University Press, 2018